Osoznannaia neobkhodimost' . Osoznannaia neobkhodimost' . Recognized Necessity . Осознанная необходимость - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Program on slavery, including child slavery and forced labor. Series description: Crime news, reports on the work of law enforcement, investigative reporting. Передача обсуждает человеческое рабство в том числе детское рабство, и принудительную работу. Описание серии: Криминальная хроника, репортажи о работе правоохранительных органов, журналистские расследования.